Dielectric-property determination from measurement of magnitude of reflection and coupling coefficients of coupled antennas - Mearnchu, Jhirat; Limpiti, Thunyawat; Torrungrueng, Danai; Akkaraekthalin, Prayoot; Krairiksh, Monai (My University, 2008)
This paper presents a dielectric-property determination technique that measures the magnitudes of the reflection and coupling coefficients of coupled antennas. They are plotted on the ε′r ε″ r plane, and the intersection of these two quantities provides the values of ε′r and ε″r where ε′r is the real part and ε″r is the imaginary part of the relative complex permittivity. Measurement results of water validate the effectiveness of the proposed technique. This technique provides a compact measurement system and is suitable for localized dielectric determination. ©2008 IEEE.
Keywords: Coupled antennas; Coupling coefficient; Dielectric-property determination; Magnitude measurement; Reflection coefficient